Antecedents of constitutional property rights in the Italian Republic: from Roman rigorism to Thomas Hobbes’ utilitarianism - Kamińska, Agnieszka (Studia Iuridica Toruniensia, 2022)
The Italian concept of ownership, enshrined in Art. 42 of the Constitution of 1947, has rich and varied juridical and philosophical antecedents. It developed in an area that is culturally and civilizationally identical to the core area of the Roman Empire. It drew mainly from the achievements of Roman jurisprudence. Staying in the circle of the Catholic tradition of Christianity, it refers to pro-social and anthropocentric threads of Thomism and medieval Christian thought. It was no stranger to the thoughts of utilitarian philosophy (Thomas Hobbes) and John Locke’s “Self-Ownership”.